Systematic Approaches to Advanced Information Flow Analysis - and Applications to Software Security - Mohr, Martin (KIT Scientific Publishing, 2023)
I report on applications of slicing and program dependence graphs (PDGs) to software security. Moreover, I propose a framework that generalizes both data-flow analysis on control-flow graphs and slicing on PDGs. This framework can be used to systematically derive data-flow-like analyses on PDGs that go beyond slicing. I demonstrate that data-flow analysis can be systematically applied to PDGs and show the practicability of my approach.